2012
DOI: 10.1186/1755-8166-5-11
|View full text |Cite
|
Sign up to set email alerts
|

High rates of de novo 15q11q13 inversions in human spermatozoa

Abstract: Low-Copy Repeats predispose the 15q11-q13 region to non-allelic homologous recombination. We have already demonstrated that a significant percentage of Prader-Willi syndrome (PWS) fathers have an increased susceptibility to generate 15q11q13 deletions in spermatozoa, suggesting the participation of intrachromatid exchanges. This work has been focused on assessing the incidence of de novo 15q11q13 inversions in spermatozoa of control donors and PWS fathers in order to determine the basal rates of inversions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…We considered the over-dominant model because the presence of an inverted and a non-inverted segment may cause a secondary, deleterious rearrangement (Feuk 2010; Osborne et al 2001; Gimelli et al 2003; Molina et al 2012). Compared to the full model, an over-dominant model should have a greater power because the inversion heterozygous are compared to a pool of the two homozygous.…”
Section: Resultsmentioning
confidence: 99%
“…We considered the over-dominant model because the presence of an inverted and a non-inverted segment may cause a secondary, deleterious rearrangement (Feuk 2010; Osborne et al 2001; Gimelli et al 2003; Molina et al 2012). Compared to the full model, an over-dominant model should have a greater power because the inversion heterozygous are compared to a pool of the two homozygous.…”
Section: Resultsmentioning
confidence: 99%
“…It is reasonable to assume that features present in addition to PRDM9‐binding sites, such as structural variants (CNVs) of the recombining paralogs or chromatin accessibility, can also influence NAHR frequency (Antonacci et al., ; Carvalho & Lupski, ; Cuscó et al., ; Vergés, Molina, Geán, Vidal, & Blanco, , ). Polymorphic large inversions present in the transmitting parents have been identified that predispose to NAHR‐mediated rearrangements involving a number of different human genes (Antonacci et al., ; Bayés, Magano, Rivera, Flores, & Pérez Jurado, ; Gimelli et al., ; Hobart et al., ; Koolen et al., ; Molina, Anton, Vidal, & Blanco, ; Osborne et al., ; Scherer et al., ; Sharp et al., ; Small, Iber, & Warren, ; Visser et al., ). Further studies will be required to investigate whether polymorphic CNVs within the paralogs or inversions of the regions located between the paralogs involved in NAHR occur disproportionately more often in the transmitting parents of patients with type‐1 NF1 deletions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in several recurrent genomic disorders, some haplotypes have been suggested to predispose to NAHR events. In this sense, inversions of the critical regions have been reported in the fathers of children affected by deletion syndromes: Williams-Beuren [ 18 - 20 ], Prader-Willi [ 21 ], Angelman [ 22 ], Smith-Magenis [ 23 ] and 17q21.31 microdeletion [ 24 ], among several others [ 25 ]. In addition, copy number variations in the LCRs which flank critical regions have been described in fathers with affected offspring: Smith-Magenis syndrome [ 26 ], Williams-Beuren syndrome [ 27 ] or 16p12.1 microdeletion disease [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) based methodologies in decondensed sperm nuclei allow the identification of gametes carrying deletions, duplications and inversions with a high sensitivity and specificity [ 21 , 35 , 36 ]. These interphase analyses, carried out in a large number of spermatozoa, offers the possibility of performing cell by cell analyses, thus assessing the incidence of rare events such as NAHR, and to establish a direct relationship between the genomic architecture and chromosomal instability during meiosis.…”
Section: Introductionmentioning
confidence: 99%